Associations of the Dietary Iron, Copper, and Selenium Level With Metabolic Syndrome: A Meta-Analysis of Observational Studies - Ding, Jun; Liu, Qi; Liu, Ze; Guo, Hongbin; Liang, Jieyu; Zhang, Yi (Frontiers in Nutrition, 2022)
Background: Epidemiological studies have investigated the associations of dietary iron, copper and selenium level with metabolic syndrome (MetS). However, their results are conflicting. This meta-analysis of observational study was therefore employed to investigate the associations above. Methods: A comprehensive literature search was employed using PubMed, Web of Science, Embase and Scopus database up to October 2021 (no restriction was set for the initiate time). The pooled relative risk (RR) of MetS for the highest versus lowest dietary iron, copper and selenium level were estimated, respectively. Results: A total of 14 observational studies (55131 participants) were identified as meeting the inclusion criteria. Specifically, 7 studies were related to the dietary iron level. The overall multi-variable adjusted RR demonstrated that the dietary iron level was positively associated with MetS (RR=1.27, 95%CI: 1.12 to 1.44; P<0.001). With regard to the dietary copper level, 7 studies were included for meta-analysis. The overall multi-variable adjusted RR showed that the dietary copper level was inversely associated with MetS (RR=0.85, 95%CI: 0.78 to 0.93; P<0.001). In addition, 4 studies were specified for the dietary selenium level. The overall multi-variable adjusted RR indicated that the dietary selenium level was inversely associated with MetS (RR=0.77, 95%CI: 0.63 to 0.95; P=0.01) as well. Conclusions: Our results suggest that the dietary iron level is positively associated with MetS, whereas a negative association between dietary copper and selenium level and MetS is obtained. Further large well-designed prospective cohort studies are warranted to elaborate the issues examined in this study.